中国建材产业发展策略问题研究 = Strategical issues for the development of China's construction materials industry - 许爱朝 Xu, Aichao (2008)
On the basis of the fundamental principles of industrial economics, this dissertation explores the industry’s market structure, economies of scale, and resource allocation, and analyses the issues that have hindered the competition and development of the industry. This dissertation also gives some suggestions on the development strategy and policy prescriptions.